ANALISIS KINERJA WIRAUSAHA SERTA VARIABEL – VARIABEL YANG MEMPENGARUHI - Kusnilawati, Nunik; Nurhidayati, Nurhidayati (FEB Universitas Sam Ratulangi Manado, 2020)
Literature review suggests that there is a relationship between competence, motivation, interests, entrepreneurial orientation and entrepreneurial performance. The purpose of the study is to analyze entrepreneurial performance by placing competence, motivation and interest as independent variables, and entrepreneurial performance as the dependent variable. While entrepreneurship orientation is positioned as an intervening variable. A sample of 150 respondents, the instrument used was a questionnaire. Likert scale measurement scale, data processing and analysis tools using SEM. There are 7 hypotheses that must be tested for truth, and the test results show that the seven hypotheses are acceptable, so the initial assumptions about the relationship between the variables tested are true. Each variable of competence, motivation and interest influences / significantly affects entrepreneurial performance and also influences / significantly through the entrepreneurial orientation variable